1977
DOI: 10.1073/pnas.74.4.1622
|View full text |Cite
|
Sign up to set email alerts
|

Absence of a measurable G2 phase in two Chinese hamster cell lines.

Abstract: Evidence is resented that demonstrates the absence of a measurable G2 prase in the cell cycles of two sublines of the Chinese hamster lung fibroblast V79. One of the sublines, in addition, lacks a detectable G1 phase, thereby possessing a cell cycle comprised of simply two phases, DNA synthesis (S) and mitosis (M).The cell life cycle of most mammalian cells can be described in terms of four phases (1): mitosis (M), a period between mitosis and the initiation of DNA replication (G1), DNA replication (S), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…This provides an upper bound of approximately 1.75 h for the duration of the G2 phase, after subtraction of the minimum BrdU incorporation time of roughly 15 min (Hayes and Nowakowski, ). The same upper bound also applies to the triple‐labeling time, under the assumption of no G2 phase [e.g., Liskay, ], yielding a maximum duration of 5.4 days for the division cycle. Conversely, assuming that the overlap in expression between the proliferation markers (PCNA and PH3) and BrdU is just long enough to allow BrdU incorporation (i.e., 15 min), a corresponding minimum duration of 20 h can be estimated for the division cycle.…”
Section: Resultsmentioning
confidence: 99%
“…This provides an upper bound of approximately 1.75 h for the duration of the G2 phase, after subtraction of the minimum BrdU incorporation time of roughly 15 min (Hayes and Nowakowski, ). The same upper bound also applies to the triple‐labeling time, under the assumption of no G2 phase [e.g., Liskay, ], yielding a maximum duration of 5.4 days for the division cycle. Conversely, assuming that the overlap in expression between the proliferation markers (PCNA and PH3) and BrdU is just long enough to allow BrdU incorporation (i.e., 15 min), a corresponding minimum duration of 20 h can be estimated for the division cycle.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of G1 phase is also obscure. Liscay (1977) reported that V79-8 cells, a subline of Chinese hamster lung fibroblast V-79, lack a detectable G1 phase. Okuda and Kimura (1982) proposed that the preparation for DNA synthesis in untransformed fibroblastic 3Y1 cells continues from the previous cycle.…”
mentioning
confidence: 99%
“…More information will be needed on the basal levels of Z '~' ( A )~ and their cores in both tumour cells and virally infected cells compared with normal cells; and on whether Ap4A is an alarmone, induced by the cellular stresses imposed, which might, among other things, cause the constituitive synthesis of elevated levels of Ap4A. A precedent for this is the finding of a subline of the Chinese hamster lung fibroblast V79 cell line which lacks a detectable G I and Gz phase (Liskay, 1977), and whose cell cycle therefore comprises two phases, DNA synthesis and mitosis; it is found to possess a constituitively high basal level of Ap4A (about 0 3 PM), even during mitosis (Weinmann-Dorsch et al, 1984).…”
Section: (8) Utilization Of @-Substituted Adenosines For Oligoriboadementioning
confidence: 99%